Tratamiento contable del inventario del GAD del cantón Ventanas en el período 2021 – 2022. - Parreño González, Edison José (2024)
Inventories are one of the most important assets because they refer to the storage of goods that are stored for the execution of activities in a fluid manner, even more so for public institutions serving the community, therefore, this case study has the objective of knowing the treatment of the inventory account by reviewing the processes and reports in the accounting and warehouse area that lead to determining the situation of the Decentralized Autonomous Government of Ventanas in the period 2021-2022, which is carried out with the help of the methodology that correspond to the type of mixed research, the descriptive and historical method, carried out through the interview technique, applied through the interview guide and on the other hand, the observation and documentary review that give rise to the analysis of Financial statements. Consequently, it was obtained that the procedures carried out for the entry of goods into the warehouse are based on the detection of the needs of the other areas, prior notification and supporting documentation, and subsequently the project is executed. For the purpose of entering the warehouse, the accounting is specifically carried out by the accounting area. Therefore, it is concluded that there is a growth in terms of inventory in warehouse and these fluctuate a general average of 59%, between both periods the same subaccounts coded under item 1.3.01 are maintained with the exception of the existence of fuels and lubricants that are I eliminate for the last year.